Hormones - Litwack, Gerald (Academic Press is an imprint of Elsevier, 2022)
Hormones, Fourth Edition provides a report on the field of human hormones viewed in light of our current understanding of cellular and subcellular architecture, along with the molecular details of their modes of action. Comprehensive information about hormone action on canonical and non-canonical signaling pathways at cellular and subcellular level and effects on architecture and function of organ systems are discussed. All chapters in this new edition have been completely updated to cover advances in endocrinology research, which has expanded significantly in the last few years. Vast coverage of hormones not previously covered and newly discovered aspects of hormone action are also included. This new fourth edition is intended to be used by advanced undergraduates and graduate students in the biological sciences. It will also provide useful background information for health professionals, clinicians and researchers in the field of endocrinology, metabolism and biochemistry.